Should I Stay or Should I Go? An Investigation of Graduate Regional Mobility in the UK and its Impact upon Early Career Earnings - Michael Kidd; Nigel C. O'Leary; Peter J. Sloane (Institute for the Study of Labor (IZA), 2014)
This paper uses HESA data from the Destination of Leavers from Higher Education survey 2003/04 to examine whether more mobile students in terms of choice of institution and location of employment earn more than those who are less mobile. The clear finding is that mobility is associated with superior earnings outcomes, but principally through mobility as it relates to students extending their horizon of job search. A bivariate probit analysis also confirms that there is a positive relationship between regional mobility both in the choice of attending university and the choice of where to take up employment.
Keywords: J24; J31; 330; location by residence; academic institution and employment; graduates; earnings